Molecular epidemiology and pathogenicity of Wesselsbron virus circulating in Africa - Faye, Martin; Di Paola, Nicholas; Dia, Moussa; Sall, Amadou Alpha; Faye, Ousmane (Virus research, 2024)
•Twenty-five Wesselsbron virus isolates from Africa were successfully characterized.•First identification of recombination events on the genome of Wesselsbron virus.•The clade 1 Wesselsbron virus was more pathogenic and neurotropic in suckling mice.•The intramuscular route was the best transmission mode for Wesselsbron virus.•Our data provide new insights in the pathogenicity and tropism of Wesselsbron virus. Wesselsbron is a neglected, mosquito-borne zoonotic disease transmitted by several species of virus-infected Aedes mosquitoes endemic to tropical regions in Africa. It affects primarily domestic livestock species with teratogenic effects, but can jump to humans. Herein, we investigated the molecular epidemiology of Wesselsbron virus in Africa using whole genome sequencing and structural analysis, and assessed its pathogenicity and tropism through in vivo experiments. A total of twenty-five isolates collected from three countries were successfully characterized. Our study is noteworthy by identifying, for the first time, inter-clade recombination events on the genome of Wesselsbron virus. However, more investigations on the precise molecular mechanisms conducting the occurrence of recombination on the genome of Wesselsbron virus, are warranted. The identification of polymorphisms on motifs of virulence and selection pressures on major proteins showed evidence of genetic evolution for Wesselsbron virus. The clade 1 was more pathogenic and neurotropic in suckling mice and the intramuscular route was found to be the best transmission mode. Our findings also provide new insights in the pathogenicity and tropism of Wesselsbron virus, which could be useful for prevention, preparedness and future outbreak response. Considering its high prevalence in mosquito populations and the increasing number of sporadic human cases, Wesselsbron virus merits more attention in terms of prevention and preparedness, as its mosquito vectors continue to globally expand and there is no vaccine.